Respuesta :

gmany

[tex]k:\ y=m_1x+b_1\\l:\ y=m_2x+b_2\\\\l\ ||\ k\iff m_2=m_1[/tex]

[tex] 110)\ 0=-5y-x-10\ \ \ \ |+5y\\5y=-x-10\ \ \ \ |:5\\y=-\dfrac{1}{5}x-2\to\boxed{m=-\dfrac{1}{5}}\\\\111)\ -6y+18=-8x\ \ \ \ |-18\\-6y=-8x-18\ \ \ \ |:(-6)\\y=\dfrac{8}{6}x+3\to\boxed{m=\dfrac{8}{6}=\dfrac{4}{3}}\\\\112)\ 0=-y-\dfrac{1}{4}x\ \ \ \ |+y\\y=-\dfrac{1}{4}x\to\boxed{m=-\dfrac{1}{4}} [/tex]

[tex] 113)\ -6x+y-3=0\ \ \ \ |+6x\\y-3=6x\ \ \ |+3\\y=6x+3\to\boxed{m=6}\\\\114)\ -4y+3x=20\ \ \ \ |-3x\\-4y=-3x+20\ \ \ \ |:(-4)\\y=\dfrac{3}{4}x-5\to\boxed{m=\dfrac{3}{4}} [/tex]